Country of Origin Effect on Purchase Intention Towards Korean Skincare Products - Nabila Aulia Soraya Putri; Diana Sari; Kurnia Khafidatur Rafi'ah (Penerbit Goodwood, 2023)
Purpose: The purpose of this research is to investigate the effect of country of origin on purchase intention towards Korean skincare products. Further, the study examines the mediating role of perceived quality and perceived price between the relationship of country of origin and purchase intention. Research methodology: This study was gathered online survey from 140 people within Generation Z in West Java, Indonesia. Using Structural Equation Modelling (SEM) with a Partial Least Square (PLS) approach. Results: This study found that country of origin and perceived price have no influence on purchase intention, while perceived quality has a significant influence on purchase intention. However, when perceived quality is included as a mediating variable, the influence of country of origin on purchase intention becomes significant. Limitations: The study focused on specific skincare products and Generation Z demographics. Future research could explore a variety of products, markets, and generations to obtain more specific results. Contribution: The study contributes insights into decision making for skincare market players, offering practical implications for marketers to optimize and increase consumer purchasing interest.